THE PERIODIZATION FORMATION OF THE PUBLIC INFORMATION POLICY OF UKRAINE: THE CONTENTS AND THE CHRONOLOGY - Шотурма, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The relevance of researching the periodization of the development of the state information policy is concerned not only with a need to clarify the criteria and benefits of the creation and implementation of state policy, but also with the need to isolate and clear lines of information policy management.